Calculation of the equivalent conductivity of electrolytic dissolutions Kohlrausch's law modification for strong electrolytes - Reátegui Romero, Warren (2006)
The law of Kohlrausch for the calculation of the equivalent conductivity for strong electrolytes is fulfilled to diluted concentrations (c ≈ 0), under these conditions the effects of the molecular interactions become despicable and the model can explain the values experimentals. As the concentration increases the experimental datas move away of the linearity that the law proposes. To explain these desviations as a result of the increase of molecular interactions Theodore Shedlovsky proposed a modification of the law of Kohlrausch. The constant of this model in an atmosphere have been determined Solver of Microsoft Excel for twelve electrolytes, doing use of compiled experimental datas in arank of 0-1N. This constants allow to generate data and to compare them with the experimental values. The results sample that this model predicts the experimental data satisfactorily.